Study on the Displacement Effect at Cylindrical Ionization Chambers in High Energy Photon of Flat and True Beams (Journal of Bangladesh Academy of Sciences, 2018)
Absorbed dose to water determination in the clinical practice introduces several perturbations factors in ionization chamber dosimetry. Displacement perturbation is one of them, which can be corrected by introducing the chamber-specific quality correction factor (kQ) or by introducing the concept of effective point of measurement (EPOM). The EPOM is the point in the chamber at which the measured dose would be the same as the measuring depth in absence of chamber. The aim of this study was to measure the displacement effect at cylindrical ionization chambers in 6 and 10 MV flat and true photon beams. The percentage of depth doses (PDDs) were considered for determining the shift of EPOM with respect to the well established Roos chamber. The displacement effect obtained a range of 0.25 to 0.57 times r (chamber radius) both in flat and true beams, which disagreed with the TRS-398 protocol recommended constant value of 0.6r.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 227-235, 2017